2020
DOI: 10.21203/rs.3.rs-56718/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Melatonin and Propolis on Markers of Inflammation, Oxidative Stress, Clinical Outcomes, and Survival Rate in Patients with Primary Sepsis Hospitalized in Intensive Care Unit: A Randomized Clinical Trial

Abstract: Background: Systemic Inflammatory Response Syndrome (SIRS) that occurs under stressful conditions affecting all organs of the body. Previous studies have shown that propolis and melatonin have the potential to improve inflammation and oxidative stress, so the aim of this study was to investigate the effects of these supplements on SIRS treatment.Method: This was a randomized, controlled clinical trial in SIRS patients comprising 55 subjects that were randomly assigned to 3 intervention or control groups. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…In addition, calcium supplements can increase the risk of nephrolithiasis and cardiovascular disease (30,31). There is a growing interest in studying the role of natural compounds in human health (2)(3)(4)(5)(6), and many studies have shown that diet and nutrients play an important role in the prevention and treatment of migraine (7)(8)(9). Dietary calcium and magnesium are safer and more convenient than supplements and should be recommended as a priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, calcium supplements can increase the risk of nephrolithiasis and cardiovascular disease (30,31). There is a growing interest in studying the role of natural compounds in human health (2)(3)(4)(5)(6), and many studies have shown that diet and nutrients play an important role in the prevention and treatment of migraine (7)(8)(9). Dietary calcium and magnesium are safer and more convenient than supplements and should be recommended as a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is influenced by many factors, such as genetic, environment, behavior, and nutrition, etc. Previous studies have shown that natural compounds play an important role in human health (2)(3)(4)(5)(6), while other studies have shown that diet and nutrients are closely related to migraine (7)(8)(9). Therefore, identifying these factors, especially modifiable ones like nutrition, may help prevent and treat migraine.…”
Section: Introductionmentioning
confidence: 99%